Penggunaan Whatsapp Group Dalam Pembelajaran Seni Tari Pada Kelas X OTKP SMK Kartika 1-2 Padang - Rahmi Syafira; Susmiarti Susmiarti (FBS Universitas Negeri Padang, 2020)
This study aims to determine and describe the use of online communication tools via whatsapp group in learning dance in class X OTKP SMK Kartika 1-2 Padang. This research is a qualitative study using a descriptive approach. The object of this research was 29 students of class X OTKP SMK Kartika 1-2 Padang. The research instrument was the researcher itself and was assisted by data collection tools such as dance videos, Whatsapp groups, and direct observation with the teacher doingthe instruction by using online learning communication tools for dance learning. The results of the research show that the use of online communication tools via WhatsApp group runs very well. Students are able to learn from any source in which at this time, the students can learn through technology / mobile phones.Students can access lessons learned such as learning dance practice on YouTube. At the second and third meetings, it can be seen that students understand and can do movements without the help of the teacher, and they can memorize only through YouTube. The last meeting also shows excellent learning outcomes. However, the teacher cannot assess the extent of the students' abilities in learning due to the fact that the teacher cannot monitor directly. Instead, the teacher can only provide direction in the form of solutions through Whatsapp group. Thus, the researcher concludes that the use of online communication tools via Whatsapp group in learning dance in class X OTKP is conducted well, and it can be used in learning dance practice.